Historical analysis of the ecumenical development in Nigeria (2018)
The attempt to embark on this study was borne out of the desire to trace the origin of ecumenical efforts in their local and global contexts. Among many Orthodox Christians,1 it is generally accepted that the contemporary Ecumenical Movement began with the Encyclical of 1920 that emanated from the Patriarch of Constantinople but historical record disproves this assertion and shows that the contemporary Ecumenical Movement has its roots in the Protestant missionary movement of the 19th century. In addition, this paper argues that ecumenical engagements were driven by the desire of Evangelical Protestants to achieve a “unity in fellowship” amongst themselves for greater success in the mission field. This contradicts the notion that ecumenism arose out of the desire for “unity in truth” or doctrinal agreement. This research becomes necessary so that the historical facts of ecumenism from global context would be put in proper perspective in order to avoid the implication that any distortion could have on ecumenical development in Nigeria which is a fall-out of the World Missionary Conference that held in Edinburgh in 1910. The objectives of this study are to bring to the fore the synergy that existed among some Protestant churches that championed ecumenical developments in Nigeria and to articulate that mission is the force that drives ecumenism both globally and locally. Using historical and sociological approaches in this study, the paper submits that since the emergence of organized ecumenism in Nigeria, there has been a paradigm shift from sustaining the legacies and vision bequeathed by the founders because modern ecumenism leadership seems to be more interested in playing politics by their actions thereby causing more disunity among the Christians in Nigeria.